Computation offloading for mobile sign language video encoding. (31st March 2020) - Chen, Xiaolei; Gao, Jianan; Zhang, Aihua; Li, Ce
Mobile sign language video encoding is a kind of application that has high computation complexity. When using this application on battery powered mobile devices, there is conflict between computation complexity of encoder and energy limitation of mobile devices. In this paper, we propose a novel computation offloading method for mobile sign language video encoding. The method utilises sufficient cloud resources for Regions Of Interest (ROI) based sign language video encoding, which is the most computation-intensive part of the whole computation offloading system. With the method, a mobile device only consumes a small portion of energy to perform other parts of the offloading system. The theoretical analysis and experimental results both demonstrate that the proposed method can reduce the processing time and energy consumption of mobile devices.